Letter (copy) : Jose Rodriguez Vega - Citrine, Walter, 1887-1983
013-0108-001 INTERNATIONAL. WJB/NS/16. PRIVATE. 27th February, 1940. Mr. Walter SCHEVENELS, International Federation of Trade Unions, 9, Avenue d'Orsay, Paris. VII. Dear Comrade Schevenels, JOSE RODRIGUEZ VEGA In reply to your letter of the 24th instant, we may say that Comrade Lamoneda (Paris) sent us at the beginning of September last information similar to that contained in your communication, namely that Comrade Vega, the former Secretary of the U.G.T., was on the point of being tried by the Courts at Madrid and being condemned to death. At our request our Foreign Secretary brought the case to the notice of the British Ambassador in Spain, who was asked to intervene. Other similar cases have been sent to us and we have made a further appeal to the Foreign Secretary. He has again written to the British Ambassador, urgently requesting him to do all he can to help Vega and the other comrades and to induce the Spanish Government to stop the present political persecution. Yours faithfully, General Secretary. 292/946/13/108